Advances in the application of sensor arrays based on nanozymes - Ying Ma; Heng Liu; Bin Li; Na Lu (Biosensors and Bioelectronics: X)
As efficient biocatalysts, enzymes can catalyze various reactions under mild conditions, and have excellent substrate specificity and selectivity. However, the high cost of preparation and difficulty in recovery of natural enzymes have seriously hindered their practical applications. Compared with natural enzymes, the nanozymes with enzyme-like activities have unique advantages in activity regulation, high stability and large-scale preparation. Nanozymes have been widely concerned in the fields of biological detection, medical treatment and cellular immunity, and have a great application potential in the sensor array field. The sensor arrays have recently received an increasing attention due to their applicability in complex biological analysis and diagnosis. This review first summarizes the classification of nanozymes and their corresponding enzyme-like activities. The applications of nanozymes in various sensor arrays are then introduced, in particular, the detecting small molecule, protein and pesticide as nonspecific recognition receptors are addressed. Finally, the future development directions and design principles are prospected for overcoming current challenges, thus providing more opportunities for the application of nanozyme sensor arrays.